Evaluasi Ketercapaian Fungsi Pasar Rakyat Waiwerang Pasca Revitalisasi - Yosef Dionisius Lamawuran; Frans Nyong (SOCIETAS, 2021)
After 2018 revitalization, Waiwerang public market hasn’t served to its’ best function, as mandated inthe 2014-7th Law of Trading. Using the Context, Input, Process, and Product (CIPP) model, this researchaims to value how the program meets public needs, the properness of resources and implementationprocess according to the plan, to evaluate the goal and change in the society, using the qualitativedescriptivedesign. Data collected by interview, observation, and documentation methods. Results showthat revitalization was irrelevant with vendors and surrounding business’ needs. Vendors’ lowparticipation during the planning process was the main cause of inaccurate needs assessment. Programimplementation was not supported with sufficient local market management’s quality and capability. Thissituation happened because of the partially interpretation of the program’s goals, which stated in the2014-7th law and 2019-2nd Law of the Ministry of Trading Affairs. Trading facilities and infrastructureswas not properly utilized in supporting the market function attainment. Shortage of kiosks number, smallsize, and air circulation, were the main caused. The change of building appearance have been achieved,however, the availability of capital and production stability by using the credit union have not beenachieved. The role of social /institutional capital in building the stability of market ecosystem was stillneglected by the market management.